Liver function tests and urinary albumin in house painters with previous heavy exposure to organic solvents. Issue 5 (May 1994) - Lundberg, I; Nise, G; Hedenborg, G; Högberg, M; Vesterberg, O
Abstract : The serum activities or concentrations of aspartate aminotransferase (ASAT), alanine aminotransferase (ALAT), alkaline phosphatase (ALP), albumin, gamma-glutamyl transpeptidase (GGT), bilirubin (BIL), cholic acid (CHOL), chenodeoxycholic acid (CHENO), and transferrin with isoelectric point 5.7, and the urinary excretion of albumin were determined among male current or former house painters (n = 135) and house carpenters (n = 71) who had worked in their trades for at least 10 years before 1970. Workers who showed a value above the 90th percentile among the carpenters in at least one of the tests ASAT, ALAT, GGT, BIL, CHOL, or CHENO were regarded as showing "possible signs of liver dysfunction". Each participant's lifetime solvent exposure was evaluated by interview. The painters were divided into categories with low, intermediate, and heavy cumulative exposure during life (LTSE) or during the most exposed year (MEYSE). All participants stated none or slight recent exposure. The prevalence of possible signs of liver dysfunction increased with solvent exposure category according to LTSE as well as MEYSE with a numerically higher risk estimate in the heavy exposure category for MEYSE than for LTSE. ALP activity increased with exposure category according to both exposure estimates. This increase seemed to be due to an interaction between exposure to solvents and current or previous long term intake of medicines potentially toxic to the liver. None of these results was affected by whether or not the subjects had been exposed to solvents during the year before the investigation. The exposure to solvents was not significantly related to any other outcome variable. It is concluded that long term heavy exposure to solvents may elicit changes in conventional liver function tests indicative of a mild chronic effect on the liver. The findings also suggest that heavy solvent exposure during short time periods is a more likely cause of the findings than lifetime cumulative solvent exposure and that an interaction between solvent exposure and medicines potentially harmful to the liver may be important in the causation of the effects.